(untitled) (Revista Latino-Americana de Enfermagem, 2019)
Objective to estimate the prevalence and avoidability of surgical adverse events in a teaching hospital and to classify the events according to the type of incident and degree of damage. Method cross-sectional retrospective study carried out in two phases. In phase I, nurses performed a retrospective review on a simple randomized sample of 192 records of adult patients using the Canadian Adverse Events Study form for case tracking. Phase II aimed at confirming the adverse event by an expert committee composed of physicians and nurses. Data were analyzed by univariate descriptive statistics. Results the prevalence of surgical adverse events was 21.8%. In 52.4% of the cases, detection occurred on outpatient return. Of the 60 cases analyzed, 90% (n = 54) were preventable and more than two thirds resulted in mild to moderate damage. Surgical technical failures contributed in approximately 40% of the cases. There was a prevalence of the infection category associated with health care (50%, n = 30). Adverse events were mostly related to surgical site infection (30%, n = 18), suture dehiscence (16.7%, n = 10) and hematoma/seroma (15%, n = 9). Conclusion the prevalence and avoidability of surgical adverse events are challenges faced by hospital management.